Physician Assistant Doctorate: A Ticket to Autonomy?. (October 2017) - Miller, Anthony A.; Coplan, Bettie
Abstract : Abstract: As the physician assistant (PA) profession celebrates 5 decades of practice, questions about the future direction of PA education and practice persist. Conversations regarding prescribing privileges have given way to debate about PA certification and the necessary level of PA education. Most PA programs already confer master's degrees, but there has been at times vigorous debate on whether or not the PA profession should join pharmacy (PharmD), physical therapy (DPT), and advanced practice nursing (DNP) and standardize education at the clinical doctorate level. The primary aim of this article is to provide historical perspective on the evolution of the PA educational degree and to discuss the potential association between credential and PA practice autonomy.